In Vitro Reduction of Antifungal Azole Sensitivity in Malassezia spp. and Resistance Prevention Strategies - Sari Almira Taria; Tutty Ariani (International Journal of Science and Society, 2026)
Malassezia spp. are lipophilic yeasts that constitute part of the normal skin flora but are also implicated in various dermatological conditions, including pityriasis versicolor, seborrheic dermatitis, and folliculitis. In recent years, decreased in vitro antifungal susceptibility has been increasingly reported, potentially contributing to therapeutic failure and disease recurrence. Literature evaluating the minimum inhibitory concentration (MIC) patterns of azole agents and the molecular mechanisms of the decreased susceptibility in Malassezia spp. remains limited. Therefore, this literature review examines scientific articles related to the antifungal susceptibility of commonly used azoles against skin infections caused by Malassezia spp. Relevant publications were analyzed, focusing on in vitro studies, minimum inhibitory concentration (MIC) values, resistance mechanisms, and strategies for preventing antifungal resistance. Several studies demonstrate increased MIC values, particularly for azole antifungals such as fluconazole and ketoconazole. Fluconazole exhibited the highest MIC values (4 to >64 mg/L; MIC50 32 mg/L; MIC90 64 mg/L), whereas posaconazole showed the lowest (0.06–2 mg/L; MIC50 0.125 mg/L; MIC90 0.5 mg/L). Ketoconazole and itraconazole demonstrated relatively good antifungal activity, while amphotericin B showed moderate efficacy. Compared to Candida spp., Malassezia spp. generally exhibited higher MIC values, suggesting reduced susceptibility. Resistance mechanisms include ERG11 gene mutations, increased efflux pump activity, and biofilm formation. Decreased antifungal susceptibility in Malassezia spp. represents an emerging clinical concern with significant implications for treatment outcomes. Rational therapeutic approaches, including antifungal stewardship, susceptibility-guided therapy, and combination strategies, are essential to prevent resistance and improve clinical effectiveness.